A component could not be larger than the whole, polyclonal immunoglobulin interference in conjugated/direct bilirubin assay and elimination: A case report - Neda Soleimani; Saeideh Khaleghpanah; Sahand Mohammadzadeh (Clinical Case Reports, 2022)
Abstract Analytical interferences (hemolysis, icterus, paraproteinemia, and lipemia) are of great concern in laboratory tests. In our case report, the conjugated bilirubin result of a patient was significantly higher than the total bilirubin. We recommend being more cautious with samples that produce indistinguishable results and attempting to resolve the issues before releasing them.